PERANAN ANALISIS SELISIH BIAYA OVERHEAD PABRIK SEBAGAI SALAH SATU ALAT PENGENDALIAN BIAYA - Lestiningsih, Amin Setio (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2009)
Factory Overhead costs are costs in addition to the cost of production of diverse types. BOP identified verydifficult, requiring accuracy cost to the product and it is very difficult to be controlled by the management.Therefore there is a need to plan and control the cost of the overhead is good. Control of factory overhead costscan be done in a way to compare between the actual BOP and BOP budget. Difference between them can bethe difference between profit and loss difference. BOP difference when the results showed the differencebetween harmful, then the company should immediately explore the causes of difference, and soon find the bestsolution to address them. However, if the difference is the difference that the company should be able tomempertahankannya that need to be increased again.Keywords: Factory Overhead Costs, Actual Factory Overhead Costs, Budget Factory Overhead Costs